Kemampuan Siswa Kelas VIIA SMP Negeri 5 Kota Kupang Dalam Menulis Teks Prosedur Berdasarkan Hasil Pengamatan Video - Pare, Evaldina; Nitbani, Samuel H.; Margareta, Karus M. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study is entitied “Ability of Class VIIA Students of SMP Negeri 5 Kota Kupang in Writing Procedur Texts Based on Video Observation Results”. This study aims to analyze and describe the ability of class VIIA students of SMP Negeri 5 Kota Kupang in writing procedur texts based on video observation results. The theory used in this study is the Theory of Writing. The method used in this study is the descriptive qualitative method. The data collection technique used in this study using the observation technique. Based on the data and resarch result s that have been obtained, it can be concluded that class VIIIA students of SMP Negeri 5 Kota Kupang are be able to write procedur texts based on the results of video observation “How to Make Soap from Aloe Vera”. The achievement can be seen from the scores obtained by student, namely students who are able to number 22 people with a percentage of 78.6% and students who are not able to number 6 people with a percentage of 21.4%.